2016
DOI: 10.18632/oncotarget.6889
|View full text |Cite
|
Sign up to set email alerts
|

MRP3 as a novel resistance factor for sorafenib in hepatocellular carcinoma

Abstract: The mechanism of resistance of hepatocellular carcinoma (HCC) to sorafenib is unknown and no useful predictive biomarker for sorafenib treatment has been reported. Accordingly, we established sorafenib-resistant HCC cells and investigated the underlying mechanism of resistance to sorafenib. Sorafenib-resistant cell lines were established from the HCC cell line PLC/PRF5 by cultivation under continuous exposure to increasing concentration of sorafenib. The IC50 values of the 2 resistant clones PLC/PRF5-R1 and PL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 33 publications
3
38
0
1
Order By: Relevance
“…In vitro and preclinical studies demonstrated that the hepatic uptake of sorafenib and its metabolites is mediated in part by organic cation transporter-1 (OCT1, encoded by gene SLC22A1 ) [3236] and by organic anion transporting polypeptide 1B1 and 1B3 (OATP1B1 and OATP1B3, encoded by gene SLCO1B1, SLCO1B3 ) [34, 35, 37]. Sorafenib also showed moderate affinity for the efflux transporter P-glycoprotein (p-gp, encoded by gene ABCB1 ) and breast cancer resistance protein (BCRP, encoded by gene ABCG2 ) [3843].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…In vitro and preclinical studies demonstrated that the hepatic uptake of sorafenib and its metabolites is mediated in part by organic cation transporter-1 (OCT1, encoded by gene SLC22A1 ) [3236] and by organic anion transporting polypeptide 1B1 and 1B3 (OATP1B1 and OATP1B3, encoded by gene SLCO1B1, SLCO1B3 ) [34, 35, 37]. Sorafenib also showed moderate affinity for the efflux transporter P-glycoprotein (p-gp, encoded by gene ABCB1 ) and breast cancer resistance protein (BCRP, encoded by gene ABCG2 ) [3843].…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Western blot analysis was performed using a rabbit anti-human PARP-1 monoclonal antibody (Cell Signaling Technology, Danvers, MA, USA) as described previously [27]. …”
Section: Methodsmentioning
confidence: 99%
“…Cell viability was assessed by using the 3-(4,5-dimethylthiazol-2yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay as described previously [27]. …”
Section: Methodsmentioning
confidence: 99%
“…Establishment of the SOR-resistant PLC/PRF5 cell line (PLC/PRF5-R2) was performed as described previously. [23] Cells were grown in Dulbecco's modified Eagle's medium (Invitrogen Sigma-Aldrich, St. Louis, MO) supplemented with 10% FBS and 2 mM L-glutamine. Cell viability was assessed via a 3-(4, 5-dimethylthiazol-2-yl)-2,5-diphenyl-2H-tetrazolium bromide (MTT) assay as described previously.…”
Section: Cell Culture and Viability Analysismentioning
confidence: 99%